Special Supplement: Global Neuro-Oncology - Syed Ather Enam; Hafiza Fatima Aziz; Kaynat Siddiqui; Mohammad Hamza Bajwa; Faiza Urooj; Saqib Kamran Bakhshi; Ahsan Ali Khan; Kee B Park; Tariq Khan (Journal of the Pakistan Medical Association, 2024)
In this special supplement of the Journal of PakistanMedical Association, titled "Global Neuro-Oncology(GNO)," we expand upon the Pakistan Brain TumourEpidemiological Study's (PBTES) foundational work.1 Thisedition is dedicated to addressing the critical challengesin global neuro-oncology, with roots in global oncologyand global surgery, as emphasized in leading publicationslike The Lancet.2 It highlights the urgency of tackling braintumours, the 10th leading cause of mortality worldwide,with a particular focus on low- and middle-incomecountries (LMICs) where healthcare disparities are most acute. Our supplement enriches the dialogue initiated by thePBTES, providing a comprehensive epidemiologicalframework that deepens our understanding of braintumour patterns in Pakistan. We go beyond these insightsby including a series of opinion articles and 15 guidelinepapers that resonate with the broader issues in globaloncology. These contributions not only echo thechallenges discussed in leading global surgery platformsbut also bridge the gap between theoreticalunderstanding and practical healthcare implementationin LMICs. The opinion pieces offer multifaceted perspectives onclinical, socioeconomic, and infrastructural challenges inLMICs. They serve as a conduit between the PBTES's datadriveninsights and the on-ground realities ofimplementing effective neuro-oncology practices inresource-constrained settings. Continue...